2021
DOI: 10.1109/access.2021.3052656
|View full text |Cite
|
Sign up to set email alerts
|

EEGNet With Ensemble Learning to Improve the Cross-Session Classification of SSVEP Based BCI From Ear-EEG

Abstract: Ear-electroencephalography (ear-EEG) using electrodes placed above hairless areas around ears is a convenient and comfortable method for signal recording in practical applications of steady-state visual evoked potential (SSVEP) based brain-computer interface (BCI). However, due to the constraint of electrode distribution behind the ear, the amplitude of SSVEP in ear-EEG signals is relatively low, which hinders the application of ear-EEG in SSVEP-based BCI. This study was aimed to improve the performance of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Additionally, [ 20 ] proposes the multiharmonic linkage CNN (MHLCNN) model for SSVEP and SSMVEP signal classifications. Furthermore, studies such as [ 10 , 15 , 26 , 28 , 53 , 56 , 63 , 64 ] utilize CNNs for person identification and improving the performance of SSVEP-based BCI systems, respectively. Researchers have employed various feature extraction methods in conjunction with their deep learning models for extracting SSVEP brain signal features.…”
Section: Systematic Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, [ 20 ] proposes the multiharmonic linkage CNN (MHLCNN) model for SSVEP and SSMVEP signal classifications. Furthermore, studies such as [ 10 , 15 , 26 , 28 , 53 , 56 , 63 , 64 ] utilize CNNs for person identification and improving the performance of SSVEP-based BCI systems, respectively. Researchers have employed various feature extraction methods in conjunction with their deep learning models for extracting SSVEP brain signal features.…”
Section: Systematic Results and Discussionmentioning
confidence: 99%
“…Unlike traditional methods, CNNs can perform automatic feature extraction and classification as an end-to-end decoding process. Several studies have demonstrated the effectiveness of using CNNs to improve the classification of scalp-EEG signals by combining EEGs from different channels and at different times through nonlinear operations on signals [ 26 ]. In the context of SSVEP, CNNs are structured with five layers: an input layer, a convolutional layer, a linear unit layer, a pooling layer, and a fully connected layer [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For ear-EEG, most took the multi-channel approach using the cEEGed platform (Debener et al, 2015 ). With up to 18 channels reading from two ears, Zhu et al ( 2021 ) achieved 81–84% accuracy with 1s window length, slightly less than >90% accuracy from scalp reading. In the work, a CCA-based SSVEP measuring from ears provided as reference was found to be only around 40–50% accurate.…”
Section: Discussionmentioning
confidence: 98%
“…Zhu applied an ensemble learning strategy to combine multiple EEGNet models with different kernel numbers together to enhance the classification accuracy of ear-EEG signals from 50.61% to 81.12% at a 1 s window length of the EEG signal. Zhu also demonstrated that the classification accuracy of the average ensemble model surpasses the accuracy of a single EEGNet model with different kernel numbers [ 54 ]. These studies show that EEGNet is an effective building block in CNN model design.…”
Section: Discussionmentioning
confidence: 99%